Efektivitas Penggunaan Rompi Pijat Oksitosin Otomatis untuk Memperlancar dan Meningkatkan Produksi ASI - Desriyanti Desriyanti; Rhesma Intan Vidiastary; Elmie Mufitana; Muhammad Arsyad Ardiansyah; Alfina Sofianawati; Fadhilah Nurul Karimah (Pusat Riset dan Inovasi Nasional, 2023)
Breast milk is nutrition for newborns, where exclusive breastfeeding will be given to babies until they are six months old. The hormone oxytocin can affect the production of breast milk. The release of the hormone oxytocin is carried out by a stimulation of the nipples through baby sucking or massage where breast massage is called breast message which can be done by a mother, or with the help of a special massage clinic to facilitate breastfeeding. The author created an Automatic Oxytocin Massage Vest to Accelerate Breast Milk Production in Breastfeeding Mothers. The strategy for implementing the vest tool can be used by the community, and knowing the level of usefulness of the tool. The next step will be knowing the effectiveness of the implementation of the vest using the